2015
DOI: 10.1016/j.jacep.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obstructive Sleep Apnea Treatment on Atrial Fibrillation Recurrence

Abstract: The use of CPAP is associated with significant reduction in recurrence of AF in patients with OSA. This effect remains consistent and similar across patient populations irrespective of whether they undergo PVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 32 publications
1
45
0
4
Order By: Relevance
“…They may be used for those who refuse or cannot tolerate CPAP and may provide an alternative to oral surgical intervention. At the very least, the patients found to be at high risk for OSA may be started on aggressive weight management therapy that can be very effective, even curative option for those who are overweight or obese [19]. Furthermore, educating patients with AF about the risks of untreated OSA may increase compliance with recommended therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may be used for those who refuse or cannot tolerate CPAP and may provide an alternative to oral surgical intervention. At the very least, the patients found to be at high risk for OSA may be started on aggressive weight management therapy that can be very effective, even curative option for those who are overweight or obese [19]. Furthermore, educating patients with AF about the risks of untreated OSA may increase compliance with recommended therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of association is strengthened by the fact that treatment of OSA with continuous positive airway pressure (CPAP) has been shown to be effective in reducing recurrence of AF [16-18]. A recent meta-analysis showed that CPAP was associated with a 42% relative risk reduction in recurrence of AF [19].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest reversibility in the arrhythmogenic substrates induced by OSA by treatment with CPAP [ 21 ]. Data from meta-analyses have shown that patients with OSA have a 25-31% increased risk for AF recurrence after catheter ablation in comparison with patients with no sleep apnea [ 28 ]. Another meta-analysis performed by Qureshi et al [ 29 ] and Shukla et al [ 28 ] in 2015 demonstrated reductions in recurrence of AF after CPAP use.…”
Section: Reviewmentioning
confidence: 99%
“…Data from meta-analyses have shown that patients with OSA have a 25-31% increased risk for AF recurrence after catheter ablation in comparison with patients with no sleep apnea [ 28 ]. Another meta-analysis performed by Qureshi et al [ 29 ] and Shukla et al [ 28 ] in 2015 demonstrated reductions in recurrence of AF after CPAP use. In another meta-analysis by Li et al, the risk of recurrence of AF increased from 31% to 57% in patients with OSA not undergoing CPAP therapy [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…A. Shukla et al в 2015 г. провели метаанализ семи проспективных исследований, включивших 1087 пациентов с ФП и обструктивным апноэ сна, которым проводилась СРАР-терапия [36]. Пациенты были разделены на две группы: больные, которым выполняли изоляцию легочных вен и которые получали медикаментозную терапию.…”
Section: основныеunclassified